The Morbid profile and clinical outcome of elderly interned for COVID-19: Epidemiology of the elderly infected by COVID-19 - de Azevedo Ferreira, Maria Izabel; Colares Maia, Luciana (Journal of Health Care, 2023)
Introduction: The elderly play an important role in the chain of transmission and contamination of the coronavirus, being the portion most likely to develop serious illness and, consequently, death. Objective: To investigate the relationship between the morbid profile and clinical outcome of the elderly infected by the coronavirus, in order to understand the relationship between these elements and their epidemiological repercussions on health. Materials and methods: This is a cross-sectional, quantitative and descriptive research carried out in a Brazilian public hospital. A total of 194 elderly people, aged 60 years or older, of any gender, race and origin, who were hospitalized due to COVID-19 infection, participated in the research. The object of the study was electronic medical records. To analyze the information collected, tabulation was performed in a spreadsheet, followed by descriptive analysis. Data were applied under logistic regression condition, using the STATA program. Results: Of the patients, 51.0% were men. Most were aged between 70-74 years (22.68%). The predominant admission symptoms were dyspnea and cough, totaling almost 100% of the complaints. The most reported comorbidity was systemic arterial hypertension, a diagnosis present in 65.46% of the analyzed medical records. The variables age and presence of comorbidity showed positive significance when related to the outcome of death. Conclusions: The population studied has particularities that must be considered in health care, adapting assistance strategies, recovery and rehabilitation of functionality, in order to maintain quality of life in old age.
Keywords: coronavirus; elderly; health care; hospitalization; Coronavirus Infections; Public Health; Health Expenditures; Coronavirus infections.